MANAGEMENT STRATEGIES TO ENHANCE COOPERATION OF INTERNATIONAL HIGHER EDUCATION INSTITUTIONS - Бебко, Світлана В. (Journal of Strategic Economic Research, 2022)
The article provides insights into the specifics and key elements in managing cooperation development among international higher education institution along with promoting the idea that cooperation contributes to boosting opportunity concentration (including the concentration in goods and services production). Apart from the above, concentration expands the opportunities associated with the so-called "scale effect" when lower per unit cost (resource amount) is incurred in product manufacturing. It is argued that the objective need to develop cooperation of economic organizations is underpinned by high dynamism of changes occurring in the contemporary product market (goods, works and services). Thus, the external environment of economic entities (including higher education institutions) is characterised by intensified global competition (in particular, due to rapid development of infrastructure, financial services, transport, informatics, communication, etc.) in the first place; secondly, by increasing uncertainty in the external environment; and finally, by a strong growing trend of market fragmentation (as a result of consumer demand differentiation, in particular). A focus is also put on the pressing global volatility and instability (in particular, triggered by economic effects of the Covid-19 pandemic). In this context, corporations have to offer their prompt response to such changes in the external settings and adapt to new realia. The findings have revealed that competition globalization encourages specialization of economic organizations, while market uncertainty and fragmentation force companies enhance their management flexibility and intensify the search for new tools and methods of product and service differentiation. The international best practice in the area of world education institutions cooperation demonstrates that among the drivers of such collaboration, and cooperation in particular, there are certain socioeconomic, legal, political, and psychological factors.